Can Competition Reduce Conflict? - Teevrat Garg; Caterina Gennaioli; Stefania Lovo; Gregor Singer (Center for Economic Studies and ifo Institute (CESifo), 2023)
We examine the effect of inter-group fiscal competition on within-group violent conflict. Using a triple difference design, we exploit exogenous variation in the degree to which villages in sub-districts compete for public funds. We find that higher competition between villages reduces conflict but only up to moderate levels of competition. The conflict-reducing effects of competition are largest in the most ethnically fractionalized and segregated villages and exist regardless of the eventual outcome of the competition. Our results are consistent with external competition favoring coordination within otherwise divided communities and boosting village identity relative to ethnic identity.
Keywords: D74; O12; H40; 330; community-driven development; competition; conflict